Bioorthogonal Probes for the Study of MDM2‐p53 Inhibitors in Cells and Development of High‐Content Screening Assays for Drug Discovery. (22nd November 2016) - D'Alessandro, Pier Luca; Buschmann, Nicole; Kaufmann, Markus; Furet, Pascal; Baysang, Frederic; Brunner, Reto; Marzinzik, Andreas; Vorherr, Thomas; Stachyra, Therese‐Marie; Ottl, Johannes; Lizos, Dimitrios E.; Cobos‐Correa, Amanda
Abstract: To study the behavior of MDM2‐p53 inhibitors in a disease‐relevant cellular model, we have developed and validated a set of bioorthogonal probes that can be fluorescently labeled in cells and used in high‐content screening assays. By using automated image analysis with single‐cell resolution, we could visualize the intracellular target binding of compounds by co‐localization and quantify target upregulation upon MDM2‐p53 inhibition in an osteosarcoma model. Additionally, we developed a high‐throughput assay to quantify target occupancy of non‐tagged MDM2‐p53 inhibitors by competition and to identify novel chemical matter. This approach could be expanded to other targets for lead discovery applications.